MITOS THE LOYAL NATIVE DAN NETRALISASI KOLONIALISME DALAM DOCUDRAMA KRAKATOA - Cherry Kartika (Universitas 17 Agustus 1945 Surabaya, 2026)
This study analyzes the BBC docu-drama film, Krakatoa: The Last Days (2006), to uncover its strategy of postcolonial representation. Employing Roland Barthes' Semiotics to identify the underlying myth and the concept of The Sublime, the focus is on the narrative markers of Willem Beijerinck (the colonial figure) and Tokaya (the loyal and intelligent native clerk). The analysis reveals that the film strategically leverages the Myth of The Loyal Native (Tokaya) – an intelligent yet subordinate native – to neutralize racial and political conflicts. This representation, paired with the Individual Humanization of Willem, functions to shift the main conflict focus from the Colonial Hierarchy to the Universal Tragedy brought by nature (The Great Equalizer). This ideological neutralization strategy subtly justifies global empathy for the colonial protagonist's narrative and softens overall criticism of the colonial structure. The findings confirm that the Tokaya character serves as narrative 'proof' that not all colonial relationships are cruel, diverting focus from structural crimes toward human helplessness in the face of nature.Keywords: Barthesian Semiotics; The Loyal Native; The Great Equalizer; Krakatoa; Colonialism